Kebijakan Kriminal Penanggulangan Kejahatan Yang Mempergunakan Media Sosial Sebagai Sarana Untuk Melakukan Kejahatan Terhadap Anak - Pantun Marojahan Simbolon; Madiasa Ablisar; Mahmud Mulyadi; Marlina Marlina (USU LAW JOURNAL, 2019)
Abstract. Criminal policy of tackling crimes against children, upload videos, or photo or negative content involving children in social media isn't enough with law No. 35/2014 jo. Act No. 23/2002 On child protection, even the presence of Act No. 11/2008 (UUITE) considered incapable of tackling crimes against children as victims in social media.  How does the subtantif policy governing crime prevention through social media as a means of committing a crime against a child, and how policy aplikatifnya, as well as tackling crime that must be done for protecting children from crime in social media. This type of research is normative, descriptive nature and preskripsi. Qualitative data analysis. Analyzing the problems of the approach of legislation (statutes aproach) and approaches (case aproach) case, not a case study or study the Court ruling. This thesis does not examine the Court ruling but described various cases ever to appear on social media about crimes against children. Policy subtantif within the UUITE that govern countermeasure of crimes against children as victims through social media still contains the classic policy model. Criminal threats on Article 45 paragraph (1) UUITE a maximum of six years is not proportional to its effects, and do not provide an alternative to other sanctions. Maximum fines or criminal sanctions, there is no minimum, so that the open space of the overthrow of the wounding a sense of criminal justice. Crime prevention policies applicable also tend to give priority to criminal proceedings. On the one hand the offender threatened/punished weighing-weigh according to article 52 paragraph (1) and section 45 subsection (1) of ACT No. 11/2008, whereas the deed the perpetrators according to law No. 35/2014 jo. Act No. 23/2002 can be resolved are versioned to find the main principles of restorative justice for the best interest for the child, not simply give priority to criminal proceedings. Subtantif policy in law No. 11/2008 should have threatened more weight than criminal threats in Act No. 35/2014 jo. Act No. 23/2002 to quell crimes against children in social media. Every child matters policies applicable in social media should pay attention to the child's best interests, rather than giving priority to different settlement matters child as a victim of criminals in social media through the process of criminal law. The policy countermeasure of the crime that must be done to protect children from the evils of distributing video, photo, or negative content in social media is to combine the efforts of the penal penal and non integrated as a the effort could not be separated in criminal policy.   Keywords : Criminal Policy, Crimes Against Children, Social Media,.